우리나라 논 이용 조류 현황 - 김미란; 남형규; 김명현; 조광진; 강기경; 나영은; Kim, Mi-Ran; Nam, Hyung-Kyu; Kim, Myung-Hyun; Cho, Kwang-Jin; Kang, Kee-Kyung; Na, Young-Eun (Hanguk hwangyeong nonghak hoeji, 2013)
BACKGROUND: Rice paddies not only produce food but also provides wildlife habitats. Although more than half agricultural land of South Korea is rice paddy, a few studies have been conducted in rice paddy ecosystem. We investigated a status of bird using a rice paddy in South Korea using published data. METHODS AND RESULTS: Birds using a rice paddy have been defined as birds which breed, rest or forage on rice paddy, bank, reservoirs or irrigation ditches. According to the publication from 1980s, birds using a rice paddy were total 47 families 279 species. Scolopacidae and Charadriidae (18%), Falconidae, Accipitridae and Strigidae (12%) and Anatidae (11%) used a rice paddy. Half of bird species using a rice paddy visited a dried rice paddy during the winter and 39.4% of them used a flooded rice paddy in spring, autumn or summer. Dependency on a rice paddy was high in ducks, egrets, cranes, and shorebirds. Population of dabbling ducks has decreased for last 12 years while cranes have increased. CONCLUSION(S): Rice paddies provide both migratory and terrestrial birds including endangered species for habitate all through the year in Korea. 본 연구에서 문헌 조사를 통하여 우리나라에서 논을 이용하는 조류의 현황을 조사하였다. 논을 이용하는 조류는 논의 본답, 논둑, 저수지 또는 관개 수로에서 번식, 휴식 또는 취식을 하는 조류로 정의하였다. 1980년대 이후부터 출판된 자료에 따르면, 논을 이용하는 조류는 총 47과 279종이었다. 도요 물떼새과(18%), 매, 수리 및 올빼미과의 맹금류(12%), 오리과 (11%)의 조류가 논을 주로 이용하였다. 논 이용 조류 중 절반은 겨울철에 건답을 이용하였으며, 39.4%는 봄이나 가을 또는 여름에 습답을 이용하는 종이었다. 논 의존도는 오리류, 백로류 및 도요류가 높았다. 수면성오리 개체군은 지난 12년 동안 감소한 반면에 두루미는 증가하는 경향을 보였다. 높은 논 의존도를 갖는 멸종위기종은 두루미, 재두루미, 검은목두루미, 흑두루미, 개리, 흰이마기러기와 따오기였다. 논은 다수의 멸종위기종을 포함하여 다양한 조류에게 사계절 내내 중요한 서식지로 제공되고 있다.